STUDI IMPLEMENTASI MACHINE VISION PADA PENGEMBANGAN PALETISASI ROBOTIK - Purwanto, Adi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2004)
Industrial robot structuris constructed by two different technology, that are mechanical component and electronic device, named mechatronic technology. Itâ€™s rapid progress is according to computer technology progress, and relevant to programmable automation system. Robot is one of the programmable automation implementation, which has multifuction and perfor to do many duty or work. Manufacturing in high competitive environment, indutries must apply felxible production methods to comply with the change of the market demand, product type, rate and production capacity, and just in time an order supply to customer. Flexible Manufacturing System (FMS), is a manufacturesystem that integrate cells in large unit, within industrial robot to serve many machine tools, with all interface connect with central computer. An important concept in manufacturing industry â€“ to support FMS â€“ is â€œjust-in-time productionâ€ (JIT), this concept will be working if service unit for component or material handling has high precission and reability. Another manufacturing system to support the flexible manufacturing are; automated guide vehicle (AGV), and automated storage/retrieval system (AS/RS). This two system can work together with robotic palletization program. Robotic palletization has been progressed to remove an uniform boxes with one size or multi size within material or component suitableto lot size or production batch. Robotic palletization progress has extend until 2D visual sensor. Implementation study need to be improved continously, appropriate to progress of manufacture industry.